Philosophical issues in the prodromal phase of psychosis. - Broome, M; Fusar-Poli, P (2012)
In this paper we try to examine some of the philosophical issues that arise from the clinical and scientific study of the prodromal phase of psychotic illness. These issues can be broadly grouped in to ethical concerns and those relating to the philosophy of psychology and science. Specifically, we discuss the notion of the prodrome as a discrete disorder as opposed to being a segment of the continuum of psychosis, and whether we can define psychopathology purely via the use of neuroscientific variables and concepts. We argue that many psychopathological terms have definitions that rely on normative notions that themselves may not be able to be reduced to terms in cognitive neuroscience and hence a purely neuroscientific conception of psychopathology and of the prodromal phase of psychosis may be unachievable. Ethical concerns arise around the treatment of 'false positives', that is, those who may clinically look to be at risk but do not develop psychosis, and the reification of a subtle research category into a DSM-5 diagnosis. More subtle issues lie in the clinical encounter where one has to balance communicating risk about developing psychosis with attempts to normalize experiences and decrease anxiety. We conclude by noting that studying the brain solely will not enable us to comprehensively understand prodromal phase of psychosis: a close attention to continua and normativity is also required and that several important clinical and ethical issues arise in both indentifying and intervening in this high risk group, and that these are now cast sharply in to focus with the inclusion of the risk syndrome in the draft DSM-5.